PROBLEM ISSUES OF THE PROFESSIONAL DEVELOPMENT OF TEACHERS IN WORKING WITH CHILDREN WITH SPECIAL EDUCATIONAL NEEDS - Олексенко, Світлана; Савченко, Світлана (Modern engineering and innovative technologies, 2024)
Inclusive education in Ukraine is becoming increasingly accessible to children with special educational needs. At the same time, this situation is a challenge for teachers who have to acquire new knowledge, skills and experience, grow professionally. The